(untitled) (Revista Plurais (e-ISSN 2238-3751), 2025)
Resumo Este estudo investiga os impactos do plano de cargos e salários sobre os colaboradores de uma cooperativa de crédito localizada em Goiânia/GO. A pesquisa foi realizada durante o processo de adequação do plano de gestão de carreira da organização ao manual do Sistema Financeiro Cooperativo ao qual está vinculada. A partir da padronização proposta pelo Programa de Gestão de Carreira por Competências com foco em Desempenho, busca-se avaliar a favorabilidade do clima organizacional à implementação. O trabalho visa promover benefícios tanto para os colaboradores quanto para a organização, utilizando conceitos organizacionais para discutir o clima interno durante a mudança do status quo. Palavras-chave: gestão de carreira; competências; padronização; clima organizacional; cooperativa de crédito. Abstract This study investigates the impact of job and salary structures on employees of a credit union located in Goiânia, Brazil. The research was conducted during the process of aligning the organization’s career management plan with the General Instructions Guide of the Cooperative Financial System to which it is affiliated. Based on the standardization proposed by the Career Management by Competencies Program focused on performance, the study aims to assess whether the organizational climate is conducive to its implementation. The research seeks to generate benefits for both employees and the organization, using organizational concepts to analyze the internal climate during a shift in the status quo. Keywords: career management; competencies; standardization; organizational climate; credit union.